KINERJA KOPERASI DENGAN PENDEKATAN BALANCED SCORECARD - desak sukarnasih (Jurnal Ilmiah Manajemen & Bisnis, 2016)
The purpose of this study was to determine and analyze the performance of Kerajinan Sari Sedana Cooperation which was seen from the perspective of Balanced Scorecard. The data of the study were collected through interviews with the help of a questionnaire approach. The design of this study used quantitative descriptive method. The results showed that the performance of the cooperation from the perspective of the financial terms of the liquidity, solvency, and profitability ratio showed the performance was still below the desired ratio standard. From the customer perspective angle as measured by Customer Acquisition and Customer Retention was pretty good. The performance of internal business process perspective and learning process with service circle efficiency and innovation showed good results. Practical implication of this study was in order to improve the performance of financial and non-financial.